An Active Learning Framework for Ecological Intelligence: Using Activities of Multiple Intelligences to Achieve Ecological Awareness - Nalan Akkuzu Güven; Melis Arzu Uyulgan (Science Education International, 2021)
The current paper aimed to identify the relation between ecological intelligence (EI) and the types of multiple intelligences (MI); and pointed out how ecological awareness could be raised through activities of MI. Data was gathered from the freshman students (N = 68) who studied at the Department of Primary Education. Four measures were used in this case study: interviews, multiple intelligence inventory (MII), ecological intelligence scale (EIS), and students' 5-min notes. Correlation analysis was used to find the relationship between the students’ ecological intelligence and the types of MI. The responses to interview questions were coded into discrete themes. Findings indicated that the intelligence type which had the most correlation with the sub-dimensions of EIS was InterP. Moreover, moderate relations were determined between the sub-dimensions of EIS and the types of MI which were Bodily/Kinesthetic (BK) and Visual/Spatial (VS). Although the students had difficulties in activities such as drama and role-playing for BK intelligence, they enjoyed, and had better motivation to learn collaboratively during the activities through visual tools. Ecological intelligence relates to various types of MI. Based on this assertion the activities of MI should be integrated in-class environmental activities for students to acquire ecological awareness and sensitivity.